Experimental Study Of Fluid Flow Behaviour And Pressure Drop In Channels Partially Filled With Metal Foams - Shikh Anuar, Fadhilah; Abdi, Iman Ashtiani; Odabaee, Mostafa; Hooman, Kamel (Elsevier Inc., 2018)
This study experimentally investigates the effects of pore density, inlet velocity and blockage ratio on fluid flow behaviour and pressure drop in channels partially filled with a metal foam block. The fluid velocities in the free stream region, which is a clear (from foam) region on the top of foam block, are measured using Laser Doppler Anemometry (LDA) and hot-wire anemometry. The metal foam data are compared to those of solid blocks with the same size. For low blockage ratios, i.e. thin foam layers, the pressure drop caused by a solid block is higher than that of the foam when tested under identical conditions. Interestingly, nonetheless, beyond a threshold blockage ratio value, the pressure drop induced by the metal foam block exceeds that of the solid block of the same height tested at the same air flow rate. This behaviour is best described as the interplay between resistance caused by blockage versus that of the wake forms downstream and over the objects and additional frictional effects within the porous region and on the interface. Furthermore, a correlation, with ±16% deviation, is developed to predict the flow resistance caused by the solid and foam blocks across the partially filled channel.